2004
DOI: 10.1103/physrevd.69.026005
|View full text |Cite
|
Sign up to set email alerts
|

Decay of type 0 Neveu-Schwarz 5-branes to nothing

Abstract: The perturbative vacuum of type 0 string theory is unstable due to the existence of the closed string tachyon. This instability can be removed by S 1 compactification with twisted boundary condition for the tachyon field. We show that even in this situation unwrapped NS5-branes are unstable and decay to bubbles of nothing smoothly without tunneling any potential barrier. We discuss a relation between the closed string tachyon condensation and the instability of NS5-branes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…The emergence of tachyonic modes indicates the instability of the spacetime. Indeed, the tachyonic mode of the deformed C 2 /Z 2 obtained in §4.2 corresponds to the instability of the spacetime against the creation of the Witten's bubble studied in [22]. The result in §4.2 confirms that this is only the unstable.…”
Section: Conclusion and Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The emergence of tachyonic modes indicates the instability of the spacetime. Indeed, the tachyonic mode of the deformed C 2 /Z 2 obtained in §4.2 corresponds to the instability of the spacetime against the creation of the Witten's bubble studied in [22]. The result in §4.2 confirms that this is only the unstable.…”
Section: Conclusion and Discussionsupporting
confidence: 54%
“…(42) We can understand the masslessness of the singlet state as a result of the B-field gauge symmetry. There is only one tachyonic state, which carries no U(1) L × U(1) R charges, and it is nothing but the unstable mode associated with the creation of a Witten's bubble discussed in [22]. We have now confirmed that this is the unique unstable mode and obtain the mass including the numerical factor, which was not obtained in [22].…”
Section: Twisted Mode Analysissupporting
confidence: 58%
See 3 more Smart Citations